COMPARATIVE CHARACTERISTICS OF SYMPTOMS IN NEUROTIC AND AFFECTIVE PATIENTS AFTER COVID-19 - Venger, O.; Koval, A. M.; Shved, M.; Ivanitska, T. (International Journal of Medicine and Medical Research, 2023)
Background. COVID-19 pandemic has negatively affected people’s mental health and created new barriers for those who have already suffered from mental illnesses. Objective. The aim of the study was to compare the symptoms of mental disorders in neurotic and affective patients, who recovered from COVID-19. Methods. The features of disorders during the pandemic in 35 neurotic and 31 affective patients were analysed. The Hamilton anxiety and depression scales (HAM-A, HAM-D), Insomnia Severity Index (ISI), Schulte tables, Jacobson short-term memory study were used. Results. Moderate and severe anxiety was more likely to develop in neurotic patients (34.29% and 37.14%, respectively), mild and moderate – in affective ones (38.71% and 32.26%). Neurotic patients had a higher level of depression (moderate – by 31.42%, severe – by 48.57%) than affective patients (mild – by 32.26%, severe – by 35.48%). The degree of memory loss was higher in affective patients (51.62% – low, 35.48% – very low) than in neurotic ones (41.94% – low, 20.00% – very low). Most of patients had reduced attention. Insomnia severity was higher in patients with neurotic disorders (25.72% – subthreshold, 45.71% – moderate) than in affective patients (38.71% – subthreshold, 22.58% – moderate). A higher level of anxiety and depression severity was observed in patients who had COVID-19 in 2021 than in those who had it in 2020, while the severity of insomnia and memory impairment – vice versa. Conclusion. Anxiety, depression, insomnia, memory and attention loss were detected. Anxiety and depression were more severe in neurotic patients but the degree of memory loss was higher in affective patients.